Pengaruh PDB, Suku Bunga, dan Nilai Total Ekspor Terhadap Investasi Asing Langsung di Indonesia (1993-2012) - Bunga, Redemta; Sukarsa, I Made (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 4, No. 8, Agustus 2015 (pp. 873-1047), 2015)
Indonesia as a developing country is not currently able to meet the development funding so that Indonesia need an injection of funds from abroad in the form of foreign direct investment. Foreign direct investment as one of the alternative financing came from overseas which can be used as additional funding recipient countries in the process of economic development. This study aims to determine the effect of GDP, interest rates, and the total value of exports to foreign direct investment in Indonesia period 1993-2012. This study uses secondary data with multiple linear regression analysis. Results of the data analysis shows simultaneously GDP, interest rates, and the value of total exports have a significant effect on foreign direct investment in Indonesia period 1993-2012. Partially GDP not significant, I nterest rate no t significant and have negative effect , and the value of total exports have a positive and significant impact on foreign direct investment in Indonesia period 1993-2012 . Then the most dominant variable effect on foreign direct investment in Indonesia 1993-2012 period is variable total value of exports.
Keywords: Foreign direct invesment, GDP, interest rate, and value of export